2018
DOI: 10.1080/02701367.2017.1411577
|View full text |Cite
|
Sign up to set email alerts
|

Energy Expenditure and Intensity of Active Video Games in Children and Adolescents

Abstract: XBOX 360 Kinect games provide energy expenditure and physical activity of moderate intensity for both genders. The use of active video games can be an interesting alternative to increase physical activity levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
3
17
0
2
Order By: Relevance
“…LightSpace, Xavix, and Sportwall showed intensive physical activity. A number of studies relate to the difference between the intensity of energy expenditure during active games and traditional exercises, indicating significant changes [30,31]. The research attempts to activate healthy adults and fight obesity, especially among young people.…”
Section: Discussionmentioning
confidence: 99%
“…LightSpace, Xavix, and Sportwall showed intensive physical activity. A number of studies relate to the difference between the intensity of energy expenditure during active games and traditional exercises, indicating significant changes [30,31]. The research attempts to activate healthy adults and fight obesity, especially among young people.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary reports present IVGs as an effective method of promoting independent physical activity. Studies comparing IVG effects with other forms of physical exercise showed that active games generated increased energy expenditure of children, which corresponded to mild, moderate, or even intensive physical activity levels [11,12,[14][15][16][17][18][19][20]. IVGs are an accessible and active form of spending free time in a home environment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies compared the effects of IVGs with other forms of physical effort, e.g. treadmill walking, and it was proven that IVGs caused a comparable or better effect in terms of the analysed parameters: energy expenditure, heart rate, percentage of heart rate reserve, and perceived effort [14,17]. In other studies, training with the use of IVGs resulted in a lesser effect than training on a treadmill.…”
Section: Interactive Video Games Vs Different Forms Of Physical Effortmentioning
confidence: 99%
See 1 more Smart Citation
“…4,[6][7][8][9][10] Although for several years videogames were criticized for being mainly a sedentary activity, today several active games have been designed to increase energy expenditure, improve cardiovascular fitness, and reduce the pandemic of sedentary behavior and obesity. [11][12][13] Pokémon Ò Go (Niantic, Inc.), is an example of an active videogame, also known as ''Exergames.'' This type of game also corresponds to the so-called ''augmented reality'' category that consists of interactive experiences between the player and the real world (i.e., the software supplements the real world with virtual or computer-generated objects that appear to coexist in the same space as the real world).…”
Section: Introductionmentioning
confidence: 99%